Effect of sustained loading on the water content of intervertebral discs: implications for disc metabolism. Issue 12 (December 1996) - McMillan, D W; Garbutt, G; Adams, M A
Abstract : OBJECTIVE: To examine regional changes in the fluid content of human intervertebral discs by comparing sagittal plane "profiles" of hydration before and after mechanical loading. METHODS: Cadaveric lumbar intervertebral discs were loaded to simulate a typical day's loading in vivo. Ten motion segments were subjected to a 1500 N compressive load for a period of 6 h with the superior vertebrae inclined by 4-8 degrees to simulate a slightly flexed posture. Immediately after loading the discs were frozen at -80 degrees C. Subsequently they were cut into slices perpendicular to the sagittal midline of the disc, and each slice was weighed before and after freeze drying. This enabled a profile of fluid content across the disc to be constructed. Fluid loss due to loading was estimated by comparing the water content of each loaded disc with that of an adjacent unloaded disc from the same spine. RESULTS: After 6 h of creep loading, disc height approached, but did not quite reach, an equilibrium. The mean fluid loss from all discs was 18%. All regions except the outer 2 mm experienced a significant loss of fluid (P < 0.01). The posterior mid-annulus showed the greatest fluid loss (30%), while the nucleus lost 15%. CONCLUSIONS: A comparison with previously published work suggests that fluid exchange of this magnitude will have a considerable effect on disc cell metabolism and on metabolite transport.